Are TIPS the “real” deal?: A conditional assessment of their role in a nominal portfolio - Hunter, Delroy M.; Simon, David P. (Journal of Banking & Finance, 2005)
This paper documents predictable time-variation in the real return beta of US Treasury Inflation Protected Securities (TIPS) and in the Sharpe ratios of both indexed and conventional bonds. The conditional mean and volatility of both bonds and their conditional correlation first are estimated from predetermined variables. These estimates then are used to compute conditional real return betas and Sharpe ratios. The time-variation in real return betas and the correlation between TIPS and nominal bonds coincides with major developments in the fixed-income market. One implication of this predictability is that portfolio managers can assess more efficiently the risk of investing in TIPS versus conventional bonds. Conditional Sharpe ratios indicate that over the sample period, TIPS had superior volatility-adjusted returns relative to nominal bonds. This finding is striking in view of the absence of a major inflation scare during the sample period from February 1997 through August 2001, but is loosely consistent with the possibility that TIPS elevated rather than reduced Treasury borrowing costs. On the other hand, mean–variance spanning tests indicate that TIPS did not enhance the mean–variance efficiency of diversified portfolios.